Immunogenicity and safety of the quadrivalent meningococcal vaccine MenACWY-TT co-administered with a combined diphtheria-tetanus-acellular pertussis vaccine versus their separate administration in adolescents and young adults: A phase III, randomized study. Issue 31 (25th July 2018) - Rivera, Luis; Schwarz, Tino F.; Kim, Kyung-Hyo; Kim, Yun-Kyung; Behre, Ulrich; Cha, Sung-Ho; Jo, Dae Sun; Lee, Jacob; Lee, Jin-Soo; Cheuvart, Brigitte; Jastorff, Archana; Van der Wielen, Marie
Highlights: We evaluated the co-administration of MenACWY-TT and Tdap in 11–25-year-olds. Co-administration did not impact immune response to MenACWY-TT, diphtheria, tetanus. Anti-pertussis antibody concentrations seemed lower following co-administration. Robust post-Tdap anti-pertussis booster responses were observed in all groups. Both vaccines had a clinically acceptable safety profile in both groups. Abstract: Background: This study evaluated the immunogenicity and safety of quadrivalent meningococcal conjugate vaccine using tetanus (T) toxoid as carrier protein (MenACWY-TT) co-administered with combined diphtheria-tetanus-acellular pertussis vaccine (Tdap) versus their separate administration in adolescents and young adults. Methods: In this phase III, randomized, partially-blind study (NCT01767376), healthy 11–25-year-olds (N = 660) were randomized (1:1:1) to receive MenACWY-TT and Tdap at Month 0 (Co-ad group), MenACWY-TT at Month 0 and Tdap at Month 1 (ACWY_Tdap group) or Tdap at Month 0 and MenACWY-TT at Month 1 (Tdap_ACWY group). Immune responses to MenACWY-TT were measured by serum bactericidal assay using rabbit complement (rSBA). Anti-diphtheria (D), anti-tetanus (T), anti-pertussis toxin (PT), anti-filamentous hemagglutinin (FHA) and anti-pertactin (PRN) antibody concentrations were assessed using enzyme-linked immunosorbent assays. Non-inferiority of immunogenicity was assessed using pre-defined clinical criteria. Safety was also evaluated. Results: Non-inferiority of immunogenicity of MenACWY-TT and Tdap when co-administered versus their separate administration was demonstrated in terms of rSBA geometric mean titers (GMTs) for 4 meningococcal serogroups and of the percentage of participants with antibody concentrations >1 IU/ml for D and T. Among the pertussis antigens, non-inferiority criteria for geometric mean concentrations (GMCs) were reached for PT, but not met for FHA and PRN. Across all groups, ≥93.2% of participants had vaccine responses to each meningococcal serogroup, ≥99.1% were seroprotected against T and D, and ≥85.5% had booster responses to each pertussis antigen. Robust increases in antibody GMTs/GMCs were observed for all antigens between pre-and post-vaccination. Both vaccines had clinically acceptable safety profiles. Conclusion: Immune responses to MenACWY-TT and to the T and D antigens from Tdap were not impacted by their co-administration. The lower antibody concentrations observed against the pertussis components may be of limited clinical relevance since robust anti-pertussis booster responses were observed. This study supports concurrent administration of the 2 vaccines in adolescents.